2007
DOI: 10.1016/j.jbiomech.2006.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of neonatal growth plate development by ex vivo intermittent mechanical stress

Abstract: Although growth plate response to mechanical stress has been increasingly studied, our understanding of mechanical modulation of neonatal growth plate is incomplete, especially concerning biochemical changes. This study was designed to explore the cellular and biochemical responses of the cranial base growth plate (CBGP) explant upon cyclic loading. The growth plate with subchondral bone was aseptically isolated from each of 24 neonatal rabbits and fixated in an organ culture system. Cyclic loading was applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
7
2
Order By: Relevance
“…11 Cyclic intermittent tension applied on the maxillae cranial base growth plate of growing rabbits resulted in significantly greater maximum growth plate height 22 and in vitro cyclic loading applied on cranial base growth plate explants caused a significant increase in the growth plate height. 28 In this study, the loss of columnar arrangement found in the dynamically loaded explants disagrees with an anterior study, which reported an enhanced columnar arrangement of the hypertrophic cells in rabbit cranial base growth plates submitted to dynamic compression. 28 In articular cartilage, it was previously shown that, under in vitro compression, aggrecan expression was significantly higher in dynamically simulated explants than in statically simulated explants.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…11 Cyclic intermittent tension applied on the maxillae cranial base growth plate of growing rabbits resulted in significantly greater maximum growth plate height 22 and in vitro cyclic loading applied on cranial base growth plate explants caused a significant increase in the growth plate height. 28 In this study, the loss of columnar arrangement found in the dynamically loaded explants disagrees with an anterior study, which reported an enhanced columnar arrangement of the hypertrophic cells in rabbit cranial base growth plates submitted to dynamic compression. 28 In articular cartilage, it was previously shown that, under in vitro compression, aggrecan expression was significantly higher in dynamically simulated explants than in statically simulated explants.…”
Section: Discussioncontrasting
confidence: 99%
“…28 In this study, the loss of columnar arrangement found in the dynamically loaded explants disagrees with an anterior study, which reported an enhanced columnar arrangement of the hypertrophic cells in rabbit cranial base growth plates submitted to dynamic compression. 28 In articular cartilage, it was previously shown that, under in vitro compression, aggrecan expression was significantly higher in dynamically simulated explants than in statically simulated explants. 29 This finding is consistent with our observations from porcine growth plates under in vitro dynamic compression in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Significant cranial abnormalities can result from premature fusion of the synchondroses, which is observed in the growth disorders achondroplasia and Crouzon syndrome (Chen et al, 2001;Perlyn et al, 2006). Recent in vitro studies have begun to shed light on the growth of synchondroses (Copray and Duterloo, 1986;Gakunga et al, 2000;Shum et al, 2003;Othman et al, 2007), but little is known about the regulation of this growth. PTHrP and its receptor are expressed in mouse embryonic and perinatal synchondroses (Dabovic et al, 2002;Young et al, 2006;Koyama et al, 2007;Nagayama et al, 2008), and PTHrP-null mice have accelerated endochondral ossification of the synchondroses at P0 (IshiiSuzuki et al, 1999).…”
mentioning
confidence: 99%